Entrepreneurship Kit (EK): the acceptance among of Business Management students / Musramaini Mustapha ... [et al.] - Mustapha, Musramaini; Azer, Ilyani; Mohamad, Siti Aishah; Md Pauzi, Suria Fadhilah; Hasan, Hazlin (2016)
UiTM acknowledged twice as entrepreneurial university by The Ministry of Education (MOE). Currently, tertiary institutions in collaboration with The Ministry of Education (MOE) have undertaken various efforts to shape the minds and intentions of students to involve in entrepreneurship activities. Therefore, it is important to create an approach to develop students' interest toward small business to practice their entrepreneurship knowledge and skills. Entrepreneurship Kit (EK) was designed to assist the students in small business practice costing. Due to that, the researchers explore the level of acceptance towards Entrepreneurship Kit (EK) among Faculty of Business Management Students. In addition, this study identifies the feedback towards Entrepreneurship Kit (EK) for future enhancement. Finding show that using EK able to help business costing record easier and users can evaluate their business performance better. With the application of Entrepreneurship Kit (EK), students are tested with hands on experience in conducting a business. Therefore, the students exposed to a better understanding of entrepreneurship in small business practice. Moreover, this Entrepreneurship Kit (EK) could inspire students and sharpen their skills in business practice.